Spatio-temporal modality and influencing factors of agribusiness survival of underdeveloped areas after the effort of reducing poverty at large scale - Zhixuan Mo; Qiangsheng Mai (Scientific Reports)
Abstract Exploring the spatiotemporal dynamics of agricultural enterprise survival and its influencing factors is of great significance for understanding the development of the agricultural industry in underdeveloped areas during and after large-scale poverty alleviation initiatives. It is also an important measure to advance work related to agriculture, rural areas, and farmers. Previous studies ignore the connection between enterprise survival and space-time and pay limited attention to the survival of agribusinesses. Therefore, based on the data of 7982 agribusiness sites in Yunnan Province of China from 2000 to 2023, this paper analyses the spatial and temporal evolution of agribusinesses using spatial econometric methods and constructs the framework of “enterprise characteristics-innovation ability-agribusiness development phase” to examine the factors influencing the survival of agribusinesses. The results show that the number of agribusinesses shows a phased increase, and agribusiness faces an “initial death trap”. The number of survivors has changed from a multiplicity of locations to a concentration centered in the central, and the hotspot area of survival time is shifted from central parts to southwestern parts. In addition, “enterprise characteristics” and “innovation ability” have a positive effect on the survival time of agribusinesses, and the “agribusiness development phase” harms their survival. Besides, there is phase heterogeneity and regional heterogeneity in the impacts. The study results provide a scientific reference for consolidating and improving the basic rural business system.